The unpredictable ways of climate change, the virocene and the future of tourism in the new normal - Korstanje, Maximiliano E.; Kulshreshtha, Sharad Kumar (Anais Brasileiros de Estudos Turísticos, 2024)
The COVID-19 pandemic has generated an unparalleled crisis in the circles of tourism industries and beyond. The overcrowding of cities associated with the technological revolution applied to transport has contributed directly to the spreading of the virus worldwide. The tourism industry has been the primary victim and spreader of COVID-19. Though initially, the consequences of the pandemic remain obscured or, at best, uncertain, no less accurate seems to be that scholars have devoted their attention to describing the economic effects on the tourism industry. For some reason, the sociological effects are unexplored in the specialized literature, which is very hard to precise here. These consequences include geopolitical tensions, cultural hostility against strangers, or even the rise of new forms of consumption associated with virtual tourism and IA. This paper discusses the host-guest encounters while basing conclusions on netnography. Since the sample was not statistically represented, the obtained results cannot be extrapolated to other universes. Netnography has received some criticism in recent years, but it remains a fertile ground for understanding certain discrimination-related issues.